Metformin attenuates myocardium dicarbonyl stress induced by chronic hypertriglyceridemia - Malinska, H; Škop, V; Trnovska, J; Markova, I; Svoboda, P; Kazdova, L; Haluzik, M (Physiological research, 2018)
Reactive dicarbonyls stimulate production of advanced glycation endproducts, increase oxidative stress and inflammation and contribute to the development of vascular complications. We measured concentrations of dicarbonyls - methylglyoxal (MG), glyoxal (GL) and 3-deoxyglucosone (3-DG) - in the heart and kidney of a model of metabolic syndrome - hereditary hypertriglyceridemic rats (HHTg) and explored its modulation by metformin. Adult HHTg rats were fed a standard diet with or without metformin (300 mg/kg b.w.) and dicarbonyl levels and metabolic parameters were measured. HHTg rats had markedly elevated serum levels of triacylglycerols (p<0.001), FFA (p<0.01) and hepatic triacylglycerols (p<0.001) along with increased concentrations of reactive dicarbonyls in myocardium (MG: p<0.001; GL: p<0.01; 3-DG: p<0.01) and kidney cortex (MG: p<0.01). Metformin treatment significantly reduced reactive dicarbonyls in the myocardium (MG: p<0.05, GL: p<0.05, 3-DG: p<0.01) along with increase of myocardial concentrations of reduced glutathione (p<0.01) and glyoxalase 1 mRNA expression (p<0.05). Metformin did not have any significant effect on dicarbonyls, glutathione or on glyoxalase 1 expression in kidney cortex. Chronically elevated hypertriglyceridemia was associated with increased levels of dicarbonyls in heart and kidney. Beneficial effects of metformin on reactive dicarbonyls and glyoxalase in the heart could contribute to its cardioprotective effects.
Keywords: fyziologický stres; glyoxal; hypertriglyceridemie; Deoxyglucose; metformin; Diet; Glyoxal; Lactoylglutathione Lyase; Metformin; krysa rodu Rattus; zvířata; Glutathione; potkani Wistar; Pyruvaldehyde; Stress, Physiological; Hypertriglyceridemia; Hypoglycemic Agents; Rats, Wistar; Male; dieta; glutathion; Rats; hypoglykemika; myokard; Animals; Myocardium; mužské pohlaví; laktoylglutathionlyasa; pyruvaldehyd; deoxyglukosa